ASSESSMENT OF THE FACTORS HINDERING THE INTERACTION BETWEEN PUBLIC AUTHORITIES AND BUSINESS STRUCTURES AT THE REGIONAL LEVEL - Berezhnaya, Vladimirovna; Boris, Olga (Revista Inclusiones, 2020)
In the article the issues related to the negative impact of factors on the interaction between public authorities and business structures at the regional level have been considered. The methodology for identifying the factors that hinder the interaction between public authorities and business structures at the regional level in the context of digitalization has been suggested and tested. The methods offered and used included qualitative (including focus groups) and quantitative (factor analysis) research. The tools for tracking digital prints have been used.